2018
DOI: 10.1038/s41598-018-30826-7
|View full text |Cite
|
Sign up to set email alerts
|

Area dependent behavior of bathocuproine (BCP) as cathode interfacial layers in organic photovoltaic cells

Abstract: Standard and inverted configuration small molecule OPV cells incorporating bathocuproine (BCP) as electron transport and exciton blocking layer is investigated, demonstrating that 2 mm2 standard and inverted cells display a maximum performance for BCP thicknesses of 10 nm and 1.5 nm, respectively. The reason for the different optimum BCP thicknesses for the two device configurations is the BCP-metal complex formed between the Ag electrode and the BCP layer in the standard configuration OPV devices. Interesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…Although both device types have identical active layers, the devices based on the standard structure show an overall better performance, reaching 130 mV higher V OC and higher PCE. Recent work has demonstrated that this trend, however, may depend on device area 41 . We note that the reported performances here are similar to those reported for bilayer DBP/C 70 cells in the literature 32,42 .…”
Section: Resultsmentioning
confidence: 99%
“…Although both device types have identical active layers, the devices based on the standard structure show an overall better performance, reaching 130 mV higher V OC and higher PCE. Recent work has demonstrated that this trend, however, may depend on device area 41 . We note that the reported performances here are similar to those reported for bilayer DBP/C 70 cells in the literature 32,42 .…”
Section: Resultsmentioning
confidence: 99%
“…Figure 2a shows an atomic force microscopy (AFM) image of 3 nm pure BCP deposited on top of an ITO coated glass substrate. The clustering of BCP occurs due to a large interface energy between ITO and BCP 33 , and may take place immediately after BCP deposition even at room temperature 34 . Such clustering can be explained by Ostwald ripening, in which some aggregates grow at the expense of others by adsorbing molecules from the surrounding surface area 45 .…”
Section: Resultsmentioning
confidence: 99%
“…Such clustering can be explained by Ostwald ripening, in which some aggregates grow at the expense of others by adsorbing molecules from the surrounding surface area 45 . At larger surface area, the probability of forming clusters that cause device shunts are larger 33 , making device upscaling more challenging in inverted OPV architectures. One possible solution to overcome BCP aggregation is to conduct co-evaporation with another organic small molecule in order to obtain smoother films 34 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations